Upaya Pengembangan Keterampilan Siswa-Siswi Terhadap Desain Produk Kreatif di SMK Negeri 01 Bengkayang - Eligia Monixa Salfarini; Yeremia Niaga Atlantika; Rissa Ayustia; Sabinus Beni; Bella Ghia Dimmera (AMMA : Jurnal Pengabdian Masyarakat, 2023)
SMK Negeri 01 Bengkayang is one of the most popular vocational high schools in Bengkayang Regency. Located in the center of Bengkayang City, SMKN 01 has several departments, one of which is the culinary department. Although they have been equipped with how to make varied food products, these students are still lacking in terms of packaging and giving stickers and product seals so that the products they produce have not been able to compete in the market. The purpose of this community service is to develop the skills of culinary students in the design of the creative products they produce so that they can compete with other products. The methods used in carrying out this community service program include providing understanding through socialization to students about the importance of product design and providing assistance to them in designing and sealing products.